The effect of calcium oxide addition in chitosan-sago composite conductivity - Liong, A. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Direct methanol fuel cell (DMFC) has been reported to comprise high promising power source which is based on polymer electrolytes membrane (PEM) using Nafion® . DMFC has been reported to be environmental friendly due to its low CO2 emission and insignificant SOx and NOx. However DMFC is hindered by some important issues such as low power density due to methanol crossover and PEM dehydrated at high temperature operation. It has also been reported that an effective DMFC membrane posses low methanol uptake and high water content. In this study, fabricated membranes for DMFC comprise of sago, chitosan and calcium oxide (CaO). Sago could facilitate the mass transport (protons and electrons) due to its hydrophilicity (water-like), while chitosan could leads to higher electrostatic interactions. Incorporating CaO as inorganic filler would result in better thermal stability. From the Scanning Electron Microscope (SEM) test that has been carried out, we found out that the addition of CaO at 20 wt% into chitosan-sago polymeric matrix increased the water uptake and lead to phase separation. On the other hand, in methanol uptake test, addition of CaO will decrease the methanol crossover thus CaO could be suggested to act as a methanol barrier. Meanwhile, the water uptake test that has been carried out showed that CaO help to facilitate sago and chitosan to absorb more water. As comparison, the voltage measurement tests were correlated with the other tests. In conclusion, chitosan-sagoCaO composite membrane has the potential to be applied in DMFC system.